On the Structural Analysis of γ-Ray Induced Primary Free Radicals in UHMWPE and Vitamin E Stabilized UHMWPE by ESR Spectroscopy - Malik Sajjad Mehmood; Muhammad Shah Jahan; Tariq Yasin; Muhammad Tariq; Mohammad Ahmad Choudhry; Masroor Ikram (Journal of Spectroscopy)
Oriented allyl radicals are detected at room temperature in gamma irradiated UHMWPE. The effects of vitamin E and storage at room temperature on this oriented structure are also investigated during the study. While testing powder as well as compression-molded solids, with or without vitamin E, a typical ESR spectrum was recorded at room temperature following 100 kGy gamma dose and subsequent storage at −78.5°C for one year. The simulated results show that the relative abundance of 5% alkyl, 68% allyl, and 27% polyenyl produced a 98.7% best fit of experimental ones. Furthermore, the allyl radical signal gives approximately 20% of random orientations and 80% of oriented molecules. In oriented PE, measured at −196°C, Ohnishi et al. (1916) observed 25 lines within a total magnetic field width of approximately 133 G. Our spectra also show 25 lines spread over 136 G in UHMWPE powder samples and at room temperature after one year of storage.